Development of E-Module Integrated with Education for Sustainable Development (ESD) on Enviromental Change Material - Husna Arifatun Najwa; Suhartini (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop an E-Module Integrated with Education for Sustainable Development (ESD) on Enviromental Change Material and determine the practicality and feasibility of the developed product. This research is a type of Research and Development (R&D) research using the Design and Development Research (D&DR) development model. The development procedure in this development model consists of 6 stages, namely identify the problem, describe the objectives, design and develop the artifact, test the artifact, evaluating testing results, and communicate the testing results. The subjects in this study were lecturer validators of material experts and media experts, biology teachers and students of class XI IPA SMA. The instruments used in this study were questionnaire instruments for validation of material experts and media experts as well as questionnaires for responses from biology teachers and students. Based on the tests that have been carried out, the media expert assessment gets a score of 76.7% with the category "feasible". The material expert assessment scored 98.3% with the category "very feasible". Biology teacher assessment scored 95% with the category "very practical", and student assessment scored 87.98% with the category "very practical". Based on the tests that have been carried out, it is known that the E-Module Integrated with Education for Sustainable Development (ESD) on Enviromental Change Material developed is feasible and practical to use as teaching material.